1990
DOI: 10.1007/bf01014102
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of phytotoxic compounds from asparagus (Asparagus officinalis L.) roots

Abstract: Potential allelochemicals from aqueous extracts of dried asparagus (Asparagus officinalis L.) roots were isolated and characterized. Active fractions separated by HPLC included ferulic, isoferulic, malic, citric, and fumaric acids. Soxhlet extraction of the residues also produced phytotoxic caffeic acid. Although none of these compounds, when applied singly, was active enough to account for the phytotoxicity of asparagus extracts, their combined effect might be additive or synergistic. An extract from lyophili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 11 publications
1
51
0
Order By: Relevance
“…This is in agreement with the HPLC results reported above. Although Hartung et al (1990) observed ferulic acid by mass spectroscopy it seems unlikely that ferulic acid is a significant contributor to inhibition by asparagus root extracts. The results from the assay of the column chromatography fractions indicate that although the phenolic and saponin fractions do inhibit root and shoot growth, the most inhibitory material occurs in the amino/carbohydrate fraction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in agreement with the HPLC results reported above. Although Hartung et al (1990) observed ferulic acid by mass spectroscopy it seems unlikely that ferulic acid is a significant contributor to inhibition by asparagus root extracts. The results from the assay of the column chromatography fractions indicate that although the phenolic and saponin fractions do inhibit root and shoot growth, the most inhibitory material occurs in the amino/carbohydrate fraction.…”
Section: Discussionmentioning
confidence: 99%
“…The isolation of tryptophan in this work, caffeic acid (Miller et al 1991) and methylenedioxycinnamic acid (Hartung et al 1990) indicate that there is more than one inhibitory compound present in root extracts. Inhibition may be the result of a number of weakly inhibitory compounds rather than a single "autotoxin".…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baravalia et al have shown the importance of polyphenols as antimicrobial compounds [23]. Polyphenols and flavonoids exhibit a wide range of biological effects and antibacterial activity [24][25][26][27]. Tannins have amazing stringent properties.…”
Section: Discussionmentioning
confidence: 99%
“…2, Table 2) and dry ( Fig. 1) weight results would be probably associated with asparagus autotoxicity which has been extensively investigated [21][22][23]. There are numerous reports of declining productivity from old asparagus plantings and extracts from asparagus tissue that had been dead for at least 8 months in the field still contained substances that retarded development of asparagus seedlings, and that the autotoxin was heat stable and water soluble [24,25].…”
Section: Autotoxicitymentioning
confidence: 99%